2007
DOI: 10.1179/174328407x213116
|View full text |Cite
|
Sign up to set email alerts
|

Welding residual stresses in ferritic power plant steels

Abstract: Many of the degradation mechanisms relevant to power plant components can be exacerbated by stresses that reside within the material. Good design or structural integrity assessments require therefore, an accounting of residual stresses, which often are introduced during welding. To do this it is necessary to characterise the stresses, but this may not be possible in thick components using non-destructive methods. These difficulties, and a paucity of relevant engineering data, have led to an increasing emphasis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
117
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 181 publications
(120 citation statements)
references
References 64 publications
3
117
0
Order By: Relevance
“…3 kg m − . The thermal conductivity and specific heat for individual phases reported in the literature depend of the authors, although follows similar trends [4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19][20][21][24][25][26][27][28][29][30][31][32][33] . The reason for such lack is due to the possibility of different features of the phases formed depending on the thermal history.…”
Section: Thermophysical Propertiesmentioning
confidence: 73%
See 3 more Smart Citations
“…3 kg m − . The thermal conductivity and specific heat for individual phases reported in the literature depend of the authors, although follows similar trends [4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19][20][21][24][25][26][27][28][29][30][31][32][33] . The reason for such lack is due to the possibility of different features of the phases formed depending on the thermal history.…”
Section: Thermophysical Propertiesmentioning
confidence: 73%
“…The available data 22 can be fitted as shown in Equation 6. However, a common approach is to assume constant emissivity during welding simulations when Equations 2 and 3 are used to dynamically impose the volumetric heat source due to the welding arc, where the heat source parameters includes the net heat transferred to the workpiece at high temperatures [5][6][7][8][9][10][11][12][13][17][18][19] . In this model, the Equation 6, obtained by regression of the data presented by Paloposki and Liedgust 22 , is used for imposing the radiative cooling boundary conditions additionally to the double ellipsoid heat flux.…”
Section: Initial and Boundary Thermal Conditionsmentioning
confidence: 99%
See 2 more Smart Citations
“…In the bcc lattice (R e ⇑), by contrast, shrinkage compensation is lower involving comparably high stress gradients. Francis et al [10] reported that displacive transformation from austenite into martensite gives higher volume change compared to reconstructive transformation of ferrite or pearlite due to a dilatation normal and a large shear strain component parallel to the habit plane in case of displasive transformation. Also, displacive transformation at low temperatures favours crystollagraphic variant selection due to higher acting stresses at these temperatures, leading to a transformation texture and anisotropic dimensional changes from what larger stress reductions can be expected.…”
mentioning
confidence: 99%